Characteristics and prognostic analysis of cystic vestibular schwannomas: prolonged surgical duration with limited impact on neurological function - Li, Xuanpeng; Cai, Hongying; Gong, Huijun; Wang, Zi’ang; Lv, Jibo (Frontiers in Oncology, 2025)
IntroductionThis study aims to evaluate the differences between cystic vestibular schwannomas (CVS) and solid vestibular schwannomas (SVS) with respect to imaging characteristics, surgical duration, gross total resection (GTR) rates, and postoperative neurological functional outcomes. The goal is to inform individualized surgical planning and perioperative management.MethodsA retrospective analysis was conducted on 273 patients who underwent surgery for vestibular schwannomas. Patient data were divided into CVS and SVS groups. Comparisons were made regarding tumor volume, surgical duration, GTR rates, and postoperative preservation of facial nerve function and hearing. Multivariate analysis was used to identify independent predictors for postoperative functional outcomes.ResultsThe findings revealed that CVS cases had larger tumor volumes and longer surgical durations (96.6 minutes vs. 87.5 minutes) compared to SVS. Additionally, the rates of postoperative facial nerve function preservation and hearing preservation were lower in the CVS group, while no significant difference was found in GTR rates between the two groups. Multivariate analysis identified tumor volume and patient age as independent predictors of postoperative functional outcomes, whereas cystic changes had a limited impact on prognosis.DiscussionThese results underscore the importance of thorough preoperative assessment of tumor volume and cystic characteristics in vestibular schwannomas. Evaluating these factors can optimize individualized surgical strategies and perioperative management, with the aim of improving postoperative functional outcomes for patients.